Custodians of the land : ecology & culture in the history of Tanzania - Maddox, Gregory; Giblin, James Leonard; Kimambo, Isaria N. (James Currey ; Ohio University Press, 2016)
Farming and pastoral societies inhabit ever-changing environments. This relationship between environment and rural culture, politics and economy in Tanzania is the subject of this volume which will be valuable in reopening debates on Tanzanian history. In his conclusion, Isaria N. Kimambo, a founding father of Tanzanian history, reflects on the efforts of successive historians to strike a balance between external causes of change and local initiative in their interpretations of Tanzanian history.
Keywords: Human ecology -- Tanzania -- History.; Environmental policy -- Tanzania.; Environmental protection -- Tanzania.; Tanzania -- Social conditions.; Tanzania -- Economic conditions.; Tanzania -- Politics and government.; Tanzanie -- Conditions sociales.; Tanzanie -- Conditions économiques.; Tanzanie -- Politique et gouvernement.; Economic history; Environmental policy; Environmental protection; Human ecology; Politics and government; Social conditions; Tanzania; History